Electromagnetic composite absorbent with multi-interface hollow structure and preparation method thereof

By adopting a multi-interface hollow structure design in the electromagnetic composite absorber, the hollow sphere of core-shell structure is generated by hydrothermal reaction and heat treatment methods, and carbon materials and metal selenide are integrated at its interface, the problems of high filling amount, low intrinsic loss and narrow broad band in the prior art are solved, and the electromagnetic wave absorption effect with low density, high intrinsic loss and wide effective absorption bandwidth are achieved.

CN119774553AActive Publication Date: 2025-04-08WUHAN UNIV OF SCI & TECH +1
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202411841483.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-13
Publication Date
2025-04-08
Estimated Expiration
2044-12-13

AI Technical Summary

Technical Problem

The existing electromagnetic composite absorbers have problems such as high filling amount, low intrinsic loss and weak absorption of narrow broadband, making it difficult to effectively achieve strong absorption of electromagnetic waves in practical applications.

Method used

An electromagnetic composite absorber with a multi-interface hollow structure is used to generate hollow spheres with core-shell structures through hydrothermal reaction and heat treatment methods, and carbon materials and metal selenides are moistened at their contact interfaces to form a multi-interface hollow structure.

Benefits of technology

The low density, high intrinsic loss and wide effective absorption bandwidth of the absorbent are achieved, which significantly improves the absorption strength and impedance matching characteristics of electromagnetic waves, and reduces the amount and manufacturing cost of absorbing materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119774553A_ABST
    Figure CN119774553A_ABST
Patent Text Reader

Abstract

The invention relates to an electromagnetic composite absorbent with a multi-interface hollow structure and a preparation method thereof. According to the technical scheme, metal salt, isopropanol and glycerinum are mixed and stirred twice, dispersion liquid is obtained, and the metal element in the metal salt is Mn or Mo or a mixture of Mn and Mo; putting the dispersion liquid into a high-pressure reaction kettle, carrying out hydrothermal reaction, drying, and carrying out annealing treatment to obtain hollow spheres; mixing water with the Tris buffer solution to obtain a mixed solution; dissolving hollow spheres in the mixed solution to obtain a turbid liquid; then mixing the turbid liquid with a carbon-nitrogen material, carrying out auto-polymerization coating, carrying out solid-liquid separation, and drying to obtain a hollow sphere with a core-shell structure; and mixing the hollow sphere with the core-shell structure with selenium powder, and carrying out heat treatment to prepare the electromagnetic composite absorbent with the multi-interface hollow structure. The method has the characteristics of high reaction safety, low absorbent filling, wide effective absorption bandwidth, high intrinsic loss and high absorption strength.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of electromagnetic composite absorbers, and in particular relates to an electromagnetic composite absorber with a multi-interface hollow structure and a preparation method thereof. Background Art

[0002] With the rapid development of electronic industry technology, the number of various electronic devices such as communications, computers, radars, and navigation has increased dramatically. As various electronic devices become more and more popular in life, they also bring serious electromagnetic radiation pollution problems. In addition, in the military field, stealth technology can improve the survival and penetration capabilities of weapons, so that one's own weapons and equipment will not be captured by the enemy's detection system. Therefore, how to overcome the problems of electromagnetic radiation and electromagnetic interference has gradually become the focus of research.

[0003] Electromagnetic composite absorbers can absorb and dissipate electromagnetic waves incident on the material, converting electromagnetic energy into other forms of energy such as heat energy, so as to effectively avoid electromagnetic wave scattering. However, traditional absorbers face a series of problems such as high density, narrow absorption bandwidth, and poor controllability, and can only achieve ideal wave absorption effects at a large filling rate and thick thickness, which limits their application areas to a certain extent. There are few studies on electromagnetic absorbers composited with metal selenides and carbon materials at multiple interfaces, or their preparation methods are relatively complicated, making it difficult to achieve broadband strong absorption characteristics.

[0004] "A preparation method of molybdenum diselenide@RGO composite material with adjustable heterostructure and multiple microwave absorption bands" (CN202210288453.3), this patented technology uses high-temperature hydrothermal reaction (220°C) to generate a composite material of molybdenum selenide and graphene to achieve three-band absorption, with a total effective absorption bandwidth of 4.12GHz and an absorbent filling ratio of 60%. The absorbent filling ratio of 60% used in the patent is difficult to achieve the low density requirement of the absorbing material. In addition, the effective absorption bandwidth of the same frequency band of the obtained absorbent is narrow, which is difficult to apply in practice.

[0005] "Manganese diselenide nanorods and their synthesis method and application" (CN201210006773.1), this patented technology synthesizes rod-shaped manganese selenide and its microwave absorption properties through a hydrothermal method. Although it achieves certain microwave absorption characteristics, its effective absorption bandwidth is narrow and difficult to implement in practical applications.

[0006] "A method for preparing a composite absorbent material of molybdenum diselenide and carbon nanotubes" (CN202011257389.X), this patented technology prepares a composite absorbent of carbon nanotubes and tin dioxide by a hydrothermal method. Although this method can achieve the preparation of lightweight absorbers, the interfacial polarization effect between tin dioxide and carbon nanotubes is weak, and it is difficult to fully exert the synergistic enhancement effect of the two materials. The intrinsic loss is low, and the corresponding electromagnetic wave loss intensity is weak.

[0007] In summary, the prior art has the technical defects of high filling amount, low intrinsic loss and weak absorption in narrow and wide band. Summary of the invention

[0008] The present invention aims to overcome the defects of the prior art and aims to provide an electromagnetic composite absorber with a multi-interface hollow structure, which has a low absorbent filling ratio, a wide effective absorption bandwidth, high intrinsic loss and high absorption intensity.

[0009] To achieve the above purpose, the technical solution adopted by the present invention is.

[0010] S1, according to the mass ratio of metal salt: isopropanol: glycerol of 1: 200-210: 66-68, the metal salt, the isopropanol and the glycerol are mixed, ultrasonically stirred for 5-10 minutes, and then continued to stir for 20-30 minutes to obtain a dispersion.

[0011] The metal element in the metal salt is Mn, or Mo, or a mixture of Mn and Mo; in the mixture, the molar ratio of Mn:Mo is 0.5-2:1.

[0012] S2, placing the dispersion into a high-pressure reactor for hydrothermal reaction; and drying and annealing the product after the hydrothermal reaction to obtain hollow spheres.

[0013] S3, mixing water and Tris buffer at a water:Tris buffer mass ratio of 10 to 20:1 to obtain a mixed solution; then dissolving the hollow spheres in the mixed solution to obtain a suspension; then mixing the suspension with the carbon-nitrogen material at a suspension:carbon-nitrogen material mass ratio of 1:0.04 to 0.06, self-polymerizing and coating, solid-liquid separation, and drying to obtain hollow spheres with a core-shell structure.

[0014] S4, mixing the hollow spheres with a core-shell structure with the selenium powder at a mass ratio of the hollow spheres with a core-shell structure to the selenium powder of 1:1-2, and then heat treating to obtain an electromagnetic composite absorber with a multi-interface hollow structure.

[0015] The carbon-nitrogen material is dopamine or phenolic resin.

[0016] The temperature of the hydrothermal reaction is 170-190° C., and the time of the hydrothermal reaction is 12-18 hours.

[0017] The drying temperature is 80-100° C., and the drying time is 12-16 hours.

[0018] The annealing treatment: the annealing temperature is 500-600° C., and the annealing time is 2-4 hours.

[0019] The heat treatment temperature is 600-800° C., and the heat treatment time is 2-3 hours.

[0020] The purity of the selenium powder is 99.9%, and the particle size of the selenium powder is ≤5 μm.

[0021] The electromagnetic composite absorber with a multi-interface hollow structure comprises metal selenide and carbon; the electromagnetic composite absorber is a core-shell structure, consisting of an inner layer and a coating layer; the material of the inner layer is metal selenide, and the mass ratio of the inner layer to the electromagnetic composite absorber is 0.4-0.5:1; the material of the coating layer is a mixture of carbon and metal selenide, and the mass ratio of carbon to metal selenide is 1:0.7-1.

[0022] Due to the adoption of the above technical solution, the present invention has the following positive effects compared with the prior art:

[0023] In the present invention, in a high temperature environment, the carbon used will undergo a reduction reaction with a metal salt or a metal oxide, capture oxygen atoms in the metal oxide, and generate a corresponding metal element. Selenium powder will also become active at high temperatures, react with the metal element, and generate a metal selenide. The present invention uses a metal selenide with a hollow structure as the inner core, and a mixture of carbon and metal selenide as the outer layer covering the inner core, and at the contact interface, the metal selenide can be embedded in the carbon material, thereby forming an electromagnetic composite absorber with a multi-interface hollow structure, which can effectively improve the dielectric loss characteristics of the absorber, effectively reduce the conductivity, and improve the impedance matching characteristics.

[0024] The electromagnetic composite absorber with a multi-interface hollow structure obtained by in-situ composite in the present invention has a relatively compact interface structure, which can enhance the interface polarization characteristics, thereby enhancing the intrinsic loss characteristics and achieving the purpose of strong electromagnetic wave absorption.

[0025] The present invention can further improve the dielectric loss and impedance matching of the material by controlling the thickness ratio of the hollow sphere and the composite layer of carbon and metal selenide, which helps to further enhance the performance of the electromagnetic composite absorber with a multi-interface hollow structure.

[0026] The electromagnetic composite absorber with a multi-interface structure of the present invention has a lower density and can be spread out in a matrix forming an absorbing material under the condition of equal mass, so that it is easier to form a surface contact effect, so that the contact area between the electromagnetic composite absorbers is significantly increased, and the particles are more easily overlapped to form a conductive network structure, which significantly improves the dielectric loss and increases the intrinsic loss characteristics, thereby greatly reducing the amount of the absorber in the absorbing material and reducing the manufacturing cost of the absorbing material.

[0027] The electromagnetic composite absorber with multi-interface hollow structure prepared by the present invention has the following detection results: the minimum reflection loss is -52.37--23.2dB; the corresponding frequency of the loss peak is 7.93-16.3GHz; the thickness is 1.75-3mm; and the effective absorption band width is 2.3-4.5GHz.

[0028] Therefore, the present invention has the characteristics of high reaction safety, low absorbent filling, wide effective absorption bandwidth, high intrinsic loss and high absorption intensity. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] Figure 1 This is a SEM image of an electromagnetic composite absorber with a multi-interface hollow structure prepared by the present invention;

[0030] Figure 2 for Figure 1 The XRD pattern of the electromagnetic composite absorber with multi-interface hollow structure is shown;

[0031] Figure 3 for Figure 1 TEM image of the electromagnetic composite absorber with multi-interface hollow structure shown;

[0032] Figure 4 for Figure 1 The reflection loss spectrum of the electromagnetic composite absorber with multi-interface hollow structure is shown;

[0033] Figure 5 This is a reflection loss spectrum of another electromagnetic composite absorber with a multi-interface hollow structure prepared by the present invention. DETAILED DESCRIPTION

[0034] For better understanding and implementation, the technical solution of the present invention will be clearly and completely described below in conjunction with the accompanying drawings and embodiments, which is not intended to limit the protection scope of the present invention.

[0035] An electromagnetic composite absorber with a multi-interface hollow structure and a preparation method thereof. The steps of the preparation method described in this specific embodiment are:

[0036] S1, according to the mass ratio of metal salt: isopropanol: glycerol of 1: 200-210: 66-68, the metal salt, the isopropanol and the glycerol are mixed, ultrasonically stirred for 5-10 minutes, and then continued to stir for 20-30 minutes to obtain a dispersion.

[0037] The metal element in the metal salt is Mn, or Mo, or a mixture of Mn and Mo; in the mixture, the molar ratio of Mn:Mo is 0.5-2:1.

[0038] S2, placing the dispersion into a high-pressure reactor for hydrothermal reaction; and drying and annealing the product after the hydrothermal reaction to obtain hollow spheres.

[0039] S3, mixing water and Tris buffer at a water:Tris buffer mass ratio of 10 to 20:1 to obtain a mixed solution; then dissolving the hollow spheres in the mixed solution to obtain a suspension; then mixing the suspension with the carbon-nitrogen material at a suspension:carbon-nitrogen material mass ratio of 1:0.04 to 0.06, self-polymerizing and coating, solid-liquid separation, and drying to obtain hollow spheres with a core-shell structure.

[0040] S4, mixing the hollow spheres with a core-shell structure with the selenium powder in a mass ratio of the hollow spheres with a core-shell structure to the selenium powder of 1:1-2, and heat treating the mixture to obtain an electromagnetic composite absorber with a multi-interface hollow structure.

[0041] The carbon-nitrogen material is dopamine or phenolic resin.

[0042] The temperature of the hydrothermal reaction is 170-190° C., and the time of the hydrothermal reaction is 12-18 hours.

[0043] The drying temperature is 80-100° C., and the drying time is 12-16 hours.

[0044] The annealing treatment: the annealing temperature is 500-600° C., and the annealing time is 2-4 hours.

[0045] The heat treatment temperature is 600-800° C., and the heat treatment time is 2-3 hours.

[0046] In this specific implementation mode:

[0047] The purity of the selenium powder is 99.9%, and the particle size of the selenium powder is ≤5 μm.

[0048] The electromagnetic composite absorber with a multi-interface hollow structure comprises metal selenide and carbon; the electromagnetic composite absorber is a core-shell structure, consisting of an inner layer and a coating layer; the material of the inner layer is metal selenide, and the mass ratio of the inner layer to the electromagnetic composite absorber is 0.4-0.5:1; the material of the coating layer is a mixture of carbon and metal selenide, and the mass ratio of carbon to metal selenide is 1:0.7-1.

[0049] This will not be described in detail in the embodiments.

[0050] Example 1

[0051] An electromagnetic composite absorber with a multi-interface hollow structure and a preparation method thereof. The steps of the preparation method described in this embodiment are:

[0052] S1, mixing the metal salt, the isopropanol and the glycerol at a mass ratio of metal salt: isopropanol: glycerol of 1: 200: 66, stirring with ultrasonic for 5 minutes, and then stirring for 20 minutes to obtain a dispersion.

[0053] The metal element in the metal salt is a mixture of Mn and Mo; in the mixture, the molar ratio of Mn:Mo is 0.5:1.

[0054] S2, placing the dispersion into a high-pressure reactor for hydrothermal reaction; and drying and annealing the product after the hydrothermal reaction to obtain hollow spheres.

[0055] S3, mixing water and the Tris buffer at a water:Tris buffer mass ratio of 10:1 to obtain a mixed solution; then dissolving the hollow spheres in the mixed solution to obtain a suspension; then mixing the suspension with the carbon-nitrogen material at a suspension:carbon-nitrogen material mass ratio of 1:0.04, self-polymerizing and coating, solid-liquid separation, and drying to obtain hollow spheres with a core-shell structure.

[0056] S4, mixing the hollow spheres with a core-shell structure with the selenium powder at a mass ratio of the hollow spheres with a core-shell structure to the selenium powder of 1:1, and then performing heat treatment to obtain an electromagnetic composite absorber with a multi-interface hollow structure.

[0057] The carbon-nitrogen material is dopamine.

[0058] The temperature of the hydrothermal reaction is 170° C., and the time of the hydrothermal reaction is 12 hours.

[0059] The drying temperature is 80° C. and the drying time is 12 hours.

[0060] The annealing treatment: the annealing temperature is 500° C. and the annealing time is 2 hours.

[0061] The heat treatment temperature is 600° C. and the heat treatment time is 2 hours.

[0062] The electromagnetic composite absorber with a multi-interface hollow structure prepared in this embodiment was tested to have the following characteristics: the minimum reflection loss was -42.87 dB; the corresponding frequency of the loss peak was 13.39 GHz; the thickness was 2 mm; and the effective absorption band width was 4.2 GHz.

[0063] Example 2

[0064] An electromagnetic composite absorber with a multi-interface hollow structure and a preparation method thereof. The steps of the preparation method described in this embodiment are:

[0065] S1, mixing the metal salt, the isopropanol and the glycerol in a mass ratio of metal salt: isopropanol: glycerol of 1: 205: 67, stirring with ultrasonic for 7 minutes, and continuing stirring for 25 minutes to obtain a dispersion.

[0066] The metal element in the metal salt is a mixture of Mn and Mo; in the mixture, the molar ratio of Mn:Mo is 1:1.

[0067] S2, placing the dispersion into a high-pressure reactor for hydrothermal reaction; and drying and annealing the product after the hydrothermal reaction to obtain hollow spheres.

[0068] S3, mixing water and the Tris buffer at a water:Tris buffer mass ratio of 20:1 to obtain a mixed solution; then dissolving the hollow spheres in the mixed solution to obtain a suspension; then mixing the suspension with the carbon-nitrogen material at a suspension:carbon-nitrogen material mass ratio of 1:0.06, self-polymerizing and coating, solid-liquid separation, and drying to obtain hollow spheres with a core-shell structure.

[0069] S4, mixing the hollow spheres with a core-shell structure with the selenium powder at a mass ratio of the hollow spheres with a core-shell structure to the selenium powder of 1:1.3, and then performing heat treatment to obtain an electromagnetic composite absorber with a multi-interface hollow structure.

[0070] The carbon-nitrogen material is dopamine.

[0071] The temperature of the hydrothermal reaction is 180° C., and the time of the hydrothermal reaction is 15 hours.

[0072] The drying temperature is 90° C. and the drying time is 15 hours.

[0073] The annealing treatment: the annealing temperature is 550° C. and the annealing time is 2.5 hours.

[0074] The heat treatment temperature is 700° C. and the heat treatment time is 2.5 hours.

[0075] The electromagnetic composite absorber with a multi-interface hollow structure prepared in this embodiment was tested to have the following characteristics: the minimum reflection loss was -18.67 dB; the corresponding frequency of the loss peak was 15.4 GHz; the thickness was 1.75 mm; and the effective absorption band width was 4.5 GHz.

[0076] Example 3

[0077] An electromagnetic composite absorber with a multi-interface hollow structure and a preparation method thereof. The steps of the preparation method described in this embodiment are:

[0078] S1, mixing the metal salt, the isopropanol and the glycerol in a mass ratio of metal salt: isopropanol: glycerol of 1:210:68, stirring with ultrasonic for 8 minutes, and further stirring for 30 minutes to obtain a dispersion.

[0079] The metal element in the metal salt is a mixture of Mn and Mo; in the mixture, the molar ratio of Mn:Mo is 1.5:1.

[0080] S2, placing the dispersion into a high-pressure reactor for hydrothermal reaction; and drying and annealing the product after the hydrothermal reaction to obtain hollow spheres.

[0081] S3, mixing water and the Tris buffer at a water:Tris buffer mass ratio of 15:1 to obtain a mixed solution; then dissolving the hollow spheres in the mixed solution to obtain a suspension; then mixing the suspension with the carbon-nitrogen material at a suspension:carbon-nitrogen material mass ratio of 1:0.045, self-polymerizing and coating, solid-liquid separation, and drying to obtain hollow spheres with a core-shell structure.

[0082] S4, mixing the hollow spheres with a core-shell structure with the selenium powder at a mass ratio of the hollow spheres with a core-shell structure to the selenium powder of 1:1.5, and then performing heat treatment to obtain an electromagnetic composite absorber with a multi-interface hollow structure.

[0083] The carbon-nitrogen material is dopamine.

[0084] The temperature of the hydrothermal reaction is 190° C., and the time of the hydrothermal reaction is 17 hours.

[0085] The drying temperature is 100° C. and the drying time is 13 hours.

[0086] The annealing treatment: the annealing temperature is 600° C. and the annealing time is 3 hours.

[0087] The heat treatment temperature is 800° C. and the heat treatment time is 3 hours.

[0088] The electromagnetic composite absorber with a multi-interface hollow structure prepared in this embodiment was tested to have the following characteristics: the minimum reflection loss was -52.37 dB; the corresponding frequency of the loss peak was 7.93 GHz; the thickness was 2.9 mm; and the effective absorption band width was 2.3 GHz.

[0089] Example 4

[0090] An electromagnetic composite absorber with a multi-interface hollow structure and a preparation method thereof. The steps of the preparation method described in this embodiment are:

[0091] S1, mixing the metal salt, the isopropanol and the glycerol in a mass ratio of metal salt: isopropanol: glycerol of 1: 203: 66.5, stirring with ultrasonic for 6 minutes, and further stirring for 27 minutes to obtain a dispersion.

[0092] The metal element in the metal salt is a mixture of Mn and Mo; in the mixture, the molar ratio of Mn:Mo is 2:1.

[0093] S2, placing the dispersion into a high-pressure reactor for hydrothermal reaction; and drying and annealing the product after the hydrothermal reaction to obtain hollow spheres.

[0094] S3, mixing water and the Tris buffer at a water:Tris buffer mass ratio of 17:1 to obtain a mixed solution; then dissolving the hollow spheres in the mixed solution to obtain a suspension; then mixing the suspension with the carbon-nitrogen material at a suspension:carbon-nitrogen material mass ratio of 1:0.055, self-polymerizing and coating, solid-liquid separation, and drying to obtain hollow spheres with a core-shell structure.

[0095] S4, mixing the hollow spheres with a core-shell structure with the selenium powder at a mass ratio of the hollow spheres with a core-shell structure to the selenium powder of 1:1.8, and then performing heat treatment to obtain an electromagnetic composite absorber with a multi-interface hollow structure.

[0096] The carbon-nitrogen material is phenolic resin.

[0097] The temperature of the hydrothermal reaction is 175° C., and the time of the hydrothermal reaction is 18 hours.

[0098] The drying temperature is 98° C. and the drying time is 16 hours.

[0099] The annealing treatment: the annealing temperature is 520° C., and the annealing time is 3.6 hours.

[0100] The heat treatment temperature is 650° C. and the heat treatment time is 2.6 hours.

[0101] The electromagnetic composite absorber with a multi-interface hollow structure prepared in this embodiment was tested to have the following characteristics: the minimum reflection loss was -30.9 dB; the corresponding frequency of the loss peak was 18 GHz; the thickness was 3 mm; and the effective absorption band width was 4.3 GHz.

[0102] Example 5

[0103] An electromagnetic composite absorber with a multi-interface hollow structure and a preparation method thereof. The steps of the preparation method described in this embodiment are:

[0104] S1, mixing the metal salt, the isopropanol and the glycerol in a mass ratio of metal salt: isopropanol: glycerol of 1: 206: 67.5, stirring with ultrasonic for 9 minutes, and further stirring for 29 minutes to obtain a dispersion.

[0105] The metal element in the metal salt is Mn.

[0106] S2, placing the dispersion into a high-pressure reactor for hydrothermal reaction; and drying and annealing the product after the hydrothermal reaction to obtain hollow spheres.

[0107] S3, mixing water and the Tris buffer at a water:Tris buffer mass ratio of 19:1 to obtain a mixed solution; then dissolving the hollow spheres in the mixed solution to obtain a suspension; then mixing the suspension with the carbon-nitrogen material at a suspension:carbon-nitrogen material mass ratio of 1:0.048, self-polymerizing and coating, solid-liquid separation, and drying to obtain hollow spheres with a core-shell structure.

[0108] S4, mixing the hollow spheres with a core-shell structure with the selenium powder at a mass ratio of the hollow spheres with a core-shell structure to the selenium powder of 1:2, and then performing heat treatment to obtain an electromagnetic composite absorber with a multi-interface hollow structure.

[0109] The carbon-nitrogen material is phenolic resin.

[0110] The temperature of the hydrothermal reaction is 185° C., and the time of the hydrothermal reaction is 16 hours.

[0111] The drying temperature is 89° C. and the drying time is 14 hours.

[0112] The annealing treatment: the annealing temperature is 580° C., and the annealing time is 2.8 hours.

[0113] The heat treatment temperature is 750° C. and the heat treatment time is 2.7 hours.

[0114] The electromagnetic composite absorber with a multi-interface hollow structure prepared in this embodiment was tested to have the following characteristics: the minimum reflection loss was -23.2 dB; the corresponding frequency of the loss peak was 16.3 GHz; the thickness was 2.5 mm; and the effective absorption band width was 3.5 GHz.

[0115] Example 6

[0116] An electromagnetic composite absorber with a multi-interface hollow structure and a preparation method thereof. The steps of the preparation method described in this embodiment are:

[0117] S1, mixing the metal salt, the isopropanol and the glycerol in a mass ratio of metal salt: isopropanol: glycerol of 1: 208: 67.2, stirring with ultrasonic for 10 minutes, and further stirring for 22 minutes to obtain a dispersion.

[0118] The metal element in the metal salt is Mo.

[0119] S2, placing the dispersion into a high-pressure reactor for hydrothermal reaction; and drying and annealing the product after the hydrothermal reaction to obtain hollow spheres.

[0120] S3, mixing water and the Tris buffer at a water:Tris buffer mass ratio of 13:1 to obtain a mixed solution; then dissolving the hollow spheres in the mixed solution to obtain a suspension; then mixing the suspension with the carbon-nitrogen material at a suspension:carbon-nitrogen material mass ratio of 1:0.053, self-polymerizing and coating, solid-liquid separation, and drying to obtain hollow spheres with a core-shell structure.

[0121] S4, mixing the hollow spheres with a core-shell structure with the selenium powder at a mass ratio of the hollow spheres with a core-shell structure to the selenium powder of 1:1.6, and then performing heat treatment to obtain an electromagnetic composite absorber with a multi-interface hollow structure.

[0122] The carbon-nitrogen material is phenolic resin.

[0123] The temperature of the hydrothermal reaction is 179° C., and the time of the hydrothermal reaction is 13 hours.

[0124] The drying temperature is 93° C. and the drying time is 15.5 hours.

[0125] The annealing treatment: the annealing temperature is 570° C. and the annealing time is 4 hours.

[0126] The heat treatment temperature is 680° C. and the heat treatment time is 2.9 hours.

[0127] The electromagnetic composite absorber with a multi-interface hollow structure prepared in this embodiment was tested to have the following characteristics: the minimum reflection loss was -23.5 dB; the corresponding frequency of the loss peak was 15.8 GHz; the thickness was 2.8 mm; and the effective absorption band width was 3.3 GHz.

[0128] Compared with the prior art, this specific implementation has the following positive effects:

[0129] In this specific embodiment, in a high temperature environment, the carbon used will undergo a reduction reaction with a metal salt or metal oxide, capture oxygen atoms in the metal oxide, and generate a corresponding metal element. Selenium powder will also become active at high temperatures, reacting with metal elements to generate metal selenides. In this specific embodiment, a metal selenide with a hollow structure is used as the core, and a mixture of carbon and metal selenide is used as the outer layer covering the core. At the contact interface, the metal selenide can be embedded in the carbon material, thereby forming an electromagnetic composite absorber with a hollow structure and multiple interfaces, which can effectively improve the dielectric loss characteristics of the absorber, effectively reduce the conductivity, and improve the impedance matching characteristics.

[0130] The electromagnetic composite absorber with a multi-interface hollow structure prepared in this specific embodiment is shown in the accompanying drawings. Figure 1 This is a SEM image of the electromagnetic composite absorber with a multi-interface hollow structure prepared in Example 2; Figure 2 for Figure 1 The XRD pattern of the electromagnetic composite absorber with multi-interface hollow structure is shown; Figure 3 for Figure 1 TEM image of the electromagnetic composite absorber with multi-interface hollow structure shown; Figure 4 for Figure 1 The reflection loss spectrum of the electromagnetic composite absorber with multi-interface hollow structure is shown; Figure 5 This is the reflection loss spectrum of the electromagnetic composite absorber with a multi-interface hollow structure prepared in Example 3.

[0131] from Figure 1 It can be seen that the prepared electromagnetic composite absorber with a multi-interface hollow structure has a spherical structure, and the sphere is a hollow structure with a relatively thin shell layer, which means that the synthesized electromagnetic composite absorber with a multi-interface hollow structure has the characteristics of low density and has a large volume share when added to the matrix material. It can achieve strong loss characteristics of electromagnetic waves when the filling content is low, thus solving the problem of high absorbent filling amount.

[0132] from Figure 2It can be seen that the components of the synthesized electromagnetic composite absorber with multi-interface hollow structure are mainly carbon materials and metal selenides (MoSe2 and MnSe) composite absorbers, among which carbon materials are conductive materials and enhance conductive losses, and metal selenides are semiconductor materials with certain electromagnetic loss characteristics. Composite with carbon materials can improve impedance matching characteristics, while increasing intrinsic loss and realizing impedance matching regulation, thus solving the problem of low loss of single absorber.

[0133] from Figure 3 It can be seen that the synthesized electromagnetic composite absorber with multi-interface hollow structure has multiple interfaces in close contact, which is conducive to enhancing the interface polarization loss characteristics and further enhancing the dielectric loss characteristics. It solves the problem of weak intrinsic loss of the absorber obtained by simple mixing and enhances the electromagnetic wave loss capacity.

[0134] from Figure 4 It can be seen that when the thickness of the absorbing material is only 1.75 mm, its corresponding effective absorption bandwidth can reach 4.5 GHz, indicating that the synthesized electromagnetic composite absorber with a multi-interface hollow structure has the characteristics of a wide effective absorption bandwidth, which effectively solves the problem of narrow absorption bandwidth.

[0135] from Figure 5 It can be seen that when the thickness of the absorbing material is only 2.9mm, the corresponding reflection loss intensity can reach -52.37dB, indicating that the synthesized hollow structure electromagnetic composite absorber has strong intrinsic loss characteristics and strong absorption characteristics. It effectively solves the problem of weak intrinsic loss of single absorber or simple mixed composite absorber in the previous case.

[0136] The multi-interface hollow structure electromagnetic composite absorber obtained by in-situ compounding in this specific embodiment has a relatively tight interface structure, which can enhance the interface polarization characteristics, thereby enhancing the intrinsic loss characteristics, and achieving the purpose of strong absorption of electromagnetic waves;

[0137] This specific embodiment can further improve the dielectric loss and impedance matching of the material by controlling the thickness ratio of the hollow sphere and the composite layer of carbon and metal selenide, which helps to further enhance the performance of the electromagnetic composite absorber;

[0138] The electromagnetic composite absorber with a multi-interface structure in this specific embodiment has a lower density and can be spread out in the matrix of the absorbing material under the condition of equal mass, so that it is easier to form a surface contact effect, so that the contact area between the electromagnetic composite absorbers is significantly increased, and the particles are more easily overlapped to form a conductive network structure, which significantly improves the dielectric loss and increases the intrinsic loss characteristics, thereby greatly reducing the amount of the absorber in the absorbing material and reducing the manufacturing cost of the absorbing material.

[0139] The electromagnetic composite absorber with a multi-interface hollow structure prepared in this specific embodiment has been tested: the minimum reflection loss is -52.37 to -23.2 dB; the corresponding frequency of the loss peak is 7.93 to 16.3 GHz; the thickness is 1.75 to 3 mm; and the effective absorption band width is 2.3 to 4.5 GHz.

[0140] Therefore, this specific embodiment has the characteristics of high reaction safety, low absorber filling, wide effective absorption bandwidth, high intrinsic loss and high absorption intensity.

Claims

1. A method for preparing an electromagnetic composite absorber having a multi-interface hollow structure, characterized in that: The steps of the preparation method are as follows: S1, mixing the metal salt, the isopropanol and the glycerol in a mass ratio of metal salt: isopropanol: glycerol of 1: 200-210: 66-68, stirring with ultrasonic waves for 5-10 minutes, and continuing stirring for 20-30 minutes to obtain a dispersion; The metal element in the metal salt is Mn, or Mo, or a mixture of Mn and Mo; in the mixture, the molar ratio of Mn:Mo is 0.5 to 2:1; S2, placing the dispersion into a high-pressure reactor for hydrothermal reaction; and drying and annealing the product after the hydrothermal reaction to obtain hollow spheres; S3, mixing water and the Tris buffer at a mass ratio of water to Tris buffer of 10 to 20:1 to obtain a mixed solution; then dissolving the hollow spheres in the mixed solution to obtain a suspension; then mixing the suspension with the carbon-nitrogen material at a mass ratio of the suspension to carbon-nitrogen material of 1:0.04 to 0.06, self-polymerizing and coating, solid-liquid separation, and drying to obtain hollow spheres with a core-shell structure; S4, mixing the hollow spheres with a core-shell structure with the selenium powder at a mass ratio of the hollow spheres with a core-shell structure to the selenium powder of 1:1-2, and then heat treating to obtain an electromagnetic composite absorber with a multi-interface hollow structure.

2. The method for preparing the electromagnetic composite absorber with a multi-interface hollow structure according to claim 1, characterized in that: The carbon-nitrogen material is dopamine or phenolic resin.

3. The method for preparing the electromagnetic composite absorber with a multi-interface hollow structure according to claim 1, characterized in that: The temperature of the hydrothermal reaction is 170-190° C., and the time of the hydrothermal reaction is 12-18 hours.

4. The method for preparing the electromagnetic composite absorber with a multi-interface hollow structure according to claim 1, characterized in that: The drying temperature is 80-100° C., and the drying time is 12-16 hours.

5. The method for preparing the electromagnetic composite absorber with a multi-interface hollow structure according to claim 1, characterized in that: The annealing treatment: the annealing temperature is 500-600° C., and the annealing time is 2-4 hours.

6. The method for preparing the electromagnetic composite absorber with a multi-interface hollow structure according to claim 1, characterized in that: The heat treatment temperature is 600-800° C., and the heat treatment time is 2-4 hours.

7. The method for preparing the electromagnetic composite absorber with a multi-interface hollow structure according to claim 1, characterized in that: The purity of the selenium powder is 99.9%, and the particle size of the selenium powder is ≤5 μm.

8. An electromagnetic composite absorber with a multi-interface hollow structure, characterized in that: The electromagnetic composite absorber with a multi-interface hollow structure is an electromagnetic composite absorber with a multi-interface hollow structure prepared by the preparation method of the electromagnetic composite absorber with a multi-interface hollow structure according to any one of claims 1 to 7; The electromagnetic composite absorber with a multi-interface hollow structure comprises metal selenide and carbon; the electromagnetic composite absorber is a core-shell structure, consisting of an inner layer and a coating layer; the material of the inner layer is metal selenide, and the mass ratio of the inner layer to the electromagnetic composite absorber is 0.4-0.5:1; the material of the coating layer is a mixture of carbon and metal selenide, and the mass ratio of carbon to metal selenide is 1:0.7-1.

Citation Information

Patent Citations

  • Manganese diselenide manometer bar as well as synthetic method and application thereof

    CN102557059B

  • Preparation method of molybdenum diselenide and carbon nanotube composite wave-absorbing material

    CN112321990A

  • Preparation method of molybdenum diselenide@RGO composite material with tunable heterostructure and multiple microwave absorption bands

    CN114639810B

  • Preparation method of ultrathin nano hollow sphere MoSe2 material

    CN109970034A

  • Hollow carbon sphere coated MoSe2 / MoO2 novel microwave absorbing material with core-shell structure and preparation method of hollow carbon sphere coated MoSe2 / MoO2 novel microwave absorbing material

    CN117163938A